FORMATION OF MILITARY PATRIOTIC EDUCATION IN YOUTH - Pulatov Anvar Narzullo ugli (Galaxy International Interdisciplinary Research Journal, 2021)
To increase and intensify the work on educating young people in the spirit of military patriotism, to more actively involve citizens of the country, governmental and nongovernmental organizations and other civil society institutions in educational work in this area and to instill in young people a sense of patriotism and courage.